Matthew Arnold (1822–1888) – prekursor pedagogiki porównawczej w XIX-wiecznej Anglii oraz jego poglądy na edukację - Włoch, Anna (Biuletyn Historii Wychowania, 2020)
The aim of the article is to present the achievements of Matthew Arnold’s in the development of European comparative education and to show his views on the changes in education in 19th century England against the background of other European countries. In the works on comparative education, a French writer Marc-Antoine Jullien de Paris (1775–1848) is regarded as one of precursors of this scientific field (currently treated as a pedagogical subdiscipline), however, as also emphasized by Józef Miąso, the British comparativists: Matthew Arnold, Thomas Darlington and Robert Morant have significantly contributed to the development of European comparative education1. The achievements of British educators, sociologists and historians in this area are underestimated and almost unknown in Poland. The development of English educational system in 19th century was different in many ways from other educational systems in continental Europe, so that the works of English comparativists, such as Matthew Arnold are unique and very important for better understanding of the historical development of comparative research methodology and also the specifics of English schools system. The article also proves that comparative education is a very important field of scientific research and played major role in planning the reforms of educational systems in many countries mainly in XIX and XX century. M. Arnold’s analyses could be still valid in XXI century. The study used the method of documental analysis, original Matthew Arnold’s works in the field of education and English-language scientific publications dealing with his achievements in the field of popularizing comparative studies. A new overview of M. Arnold’s achievement will ensure the use of sociological analyzes.